Acquired loss of cardiac vagal activity is associated with myocardial injury in patients undergoing noncardiac surgery: prospective observational mechanistic cohort study. (December 2019) - May, Shaun M.; Reyes, Anna; Martir, Gladys; Reynolds, Joseph; Paredes, Laura Gallego; Karmali, Shamir; Stephens, Robert C.M.; Brealey, David; Ackland, Gareth L.
Abstract: Background: Myocardial injury is more frequent after noncardiac surgery in patients with preoperative cardiac vagal dysfunction, as quantified by delayed heart rate (HR) recovery after cessation of cardiopulmonary exercise testing. We hypothesised that serial and dynamic measures of cardiac vagal activity are also associated with myocardial injury after noncardiac surgery. Methods: Serial autonomic measurements were made before and after surgery in patients undergoing elective noncardiac surgery. Cardiac vagal activity was quantified by HR variability and HR recovery after orthostatic challenge (supine to sitting). Revised cardiac risk index (RCRI) was calculated for each patient. The primary outcome was myocardial injury (high-sensitivity troponin ≥15 ng L −1 ) within 48 h of surgery, masked to investigators. The exposure of interest was cardiac vagal activity (high-frequency power spectral analysis [HFLn ]) and HR recovery 90 s from peak HR after the orthostatic challenge. Results: Myocardial injury occurred in 48/189 (25%) patients, in whom 41/48 (85%) RCRI was <2. In patients with myocardial injury, vagal activity (HFLn ) declined from 5.15 (95% confidence interval [CI]: 4.58–5.72) before surgery to 4.33 (95% CI: 3.76–4.90; P <0.001) 24 h after surgery. In patients who remained free of myocardial injury, HFLn did not change (4.95 [95% CI: 4.64–5.26] before surgery vs 4.76 [95% CI: 4.44–5.08] after surgery). Before and after surgery, the orthostatic HR recovery was slower in patients with myocardial injury (5 beats min −1 [95% CI: 3–7]), compared with HR recovery in patients who remained free of myocardial injury (10 beats min −1 [95% CI: 7–12]; P =0.02). Conclusions: Serial HR measures indicating loss of cardiac vagal activity are associated with perioperative myocardial injury in lower-risk patients undergoing noncardiac surgery.